Mental health in L'Aquila after the earthquake - Paolo Stratta; Stefano de Cataldo; Roberto Bonanni; Marco Valenti; Francesco Masedu; Alessandro Rossi (Istituto Superiore di Sanità, 2012)
INTRODUCTION: In the present work we describe the mental health condition of L'Aquila population in the aftermath of the earthquake in terms of structural, process and outcome perspectives. METHOD: Literature revision of the published reports on the L'Aquila earthquake has been performed. RESULTS: Although important psychological distress has been reported by the population, capacity of resilience can be observed. However if resilient mechanisms intervened in immediate aftermath of the earthquake, important dangers are conceivable in the current medium-long-term perspective due to the long-lasting alterations of day-to-day life and the disruption of social networks that can be well associated with mental health problems. CONCLUSIONS: In a condition such as an earthquake, the immediate physical, medical, and emergency rescue needs must be addressed initially. However training first responders to identify psychological distress symptoms would be important for mental health triage in the field.